The microsporidian Enterocytozoon hepatopenaei is not the cause of white feces syndrome in whiteleg shrimp Penaeus (Litopenaeus) vannamei - Amornrat Tangprasittipap (2018)
Background: The microsporidian Enterocytozoon hepatopenaei was first described from Thailand in 2009 in farmed, indigenous giant tiger shrimp Penaeus (Penaeus) monodon. The natural reservoir for the parasite is still unknown. More recently, a microsporidian closely resembling it in morphology and tissue preference was found in Thai-farmed, exotic, whiteleg shrimp Penaeus (Litopenaeus) vannamei exhibiting white feces syndrome (WFS). Our objective was to compare the newly found pathogen with E. hepatopenaei and to determine its causal relationship with WFS.Results: Generic primers used to amplify a fragment of the small subunit ribosomal RNA (ssu rRNA) gene for cloning and sequencing revealed that the new parasite from WFS ponds had 99% sequence identity to that of E. hepatopenaei, suggesting it was conspecific. Normal histological analysis using tissue sections stained with hematoxylin and eosin (H&E) revealed that relatively few tubule epithelial cells exhibited spores, suggesting that the infections were light. However, the H&E results were deceptive since nested PCR and in situ hybridization analysis based on the cloned ssu rRNA gene fragment revealed very heavy infections in tubule epithelial cells in the central region of the hepatopancreas in the absence of spores. Despite these results, high prevalence of E. hepatopenaei in shrimp from ponds not exhibiting WFS and a pond that had recovered from WFS indicated no direct causal association between these infections and WFS. This was supported by laboratory oral challenge trials that revealed direct horizontal transmission to uninfected shrimp but no signs of WFS.Conclusions: The microsporidian newly found in P. vannamei is conspecific with previously described E. hepatopenaei and it is not causally associated with WFS. However, the deceptive severity of infections (much greater than previously reported in P. monodon) would undoubtedly have a negative effect on whiteleg shrimp growth and production efficiency and this could be exacerbated by the possibility of horizontal transmission revealed by laboratory challenge tests. Thus, it is recommended that the PCR and in situ hybridization methods developed herein be used to identify the natural reservoir species so they can be eliminated from the shrimp rearing system. © 2013 Tangprasittipap et al.; licensee BioMed Central Ltd.